2016
DOI: 10.1111/tsq.12115
|View full text |Cite
|
Sign up to set email alerts
|

“Plan your Burn, Burn your Plan”: How Decentralization, Storytelling, and Communification Can Support Participatory Practices

Abstract: Research has found that compared with larger groups, small ones had fewer difficulties with retaining their participatory-democratic practices and values. However, the endurance and expansion of Burning Man, from 20 friends and family in 1986 to a temporary arts community of more than 66,000 persons in 2014, suggests that collectivities can maintain and augment participatory practices over increasing scale. Using an ethnographic study of organizing activities spanning 1998 to 2001 and follow-up research throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 60 publications
1
24
0
1
Order By: Relevance
“…'Communification' has been described as connecting an individual to a community involving a process of meaning-making through communication of symbols which can arouse strong attachments [76,77]. The forum exhibited evidence of a specific and unique language, credited as important in building solidarities [78].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…'Communification' has been described as connecting an individual to a community involving a process of meaning-making through communication of symbols which can arouse strong attachments [76,77]. The forum exhibited evidence of a specific and unique language, credited as important in building solidarities [78].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…As we see from the studies reported in this section, with practice, many of these groups have learned to be much more proficient in their consensus decision‐making practices than they used to be (Leach ). Some of these volunteer‐based groups have grown far larger than was thought possible decades ago, while finding ways to keep their decisional processes local or regional and their volunteer work relations communal (Chen ). The newer groups have managed to attract a much more diverse membership than they had in the 1970s, and some have learned how to build workplace democracy on the basis of diverse perspectives and experiences (Meyers and Vallas 2016).…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Further, research in festivals remains important as behavior and customs found at festivals can be considered exemplary of ceremony and ritual in modern society (Shrum and Kilburn ). There are relatively few sociological studies of festivals or the Burning Man festival itself (but see Adams ; Chen , , , ; Doherty ; Gotham ; Sherry and Kozinets ), however, Burning Man and associated regional burn festivals may provide insight for scholars interested in lifestyle‐based politics because of their relative longevity, counter‐cultural nature, and shared meaning and ideology (Chen ).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%